2007
DOI: 10.1016/j.cardiores.2007.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP induces assembly and activation of the myosin light chain phosphatase complex in endothelial cells☆

Abstract: The present study shows for the first time that, in endothelial cells, extracellular ATP causes activation of MLCP through recruitment of PP1delta and MYPT1 into a MLCP holoenzyme complex and PP1-mediated reduction of the inhibitory phosphorylation of MYPT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…We found that Calyculin A induced an increase in MYPT1 phosphorylation at Thr-853, which is a phosphorylation site of Rho-kinase ( Figure 2A ) . These results indicate that MYPT1 is dephosphorylated by PP1 or PP2A, in agreement with previous reports [22][24]. It is known that a 17 kDa protein kinase C (PKC)-potentiated phosphatase inhibitory protein (CPI-17), phosphorylated at Thr-38, interacts with a catalytic subunit of myosin phosphatase and suppresses myosin phosphatase activity [28].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We found that Calyculin A induced an increase in MYPT1 phosphorylation at Thr-853, which is a phosphorylation site of Rho-kinase ( Figure 2A ) . These results indicate that MYPT1 is dephosphorylated by PP1 or PP2A, in agreement with previous reports [22][24]. It is known that a 17 kDa protein kinase C (PKC)-potentiated phosphatase inhibitory protein (CPI-17), phosphorylated at Thr-38, interacts with a catalytic subunit of myosin phosphatase and suppresses myosin phosphatase activity [28].…”
Section: Resultssupporting
confidence: 92%
“…It is likely that myosin phosphatase controls phosphorylation of MYPT1 at Thr-696 or Thr-853. Furthermore, Calyculin A, an inhibitor of PP1 and PP2A, increases the phosphorylation of MYPT1 at Thr-696 and Thr-853 in vivo [22][24]. We confirmed that treatment with Calyculin A induced the phosphorylation of MYPT1 at Thr-853 ( Figure 2A ) .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There is a growing body of evidence that myosin-light-chain (MLC) kinase (MLCK) and phosphatase (MLCP) participate in the regulation of endothelial barrier function (Kolosova et al, 2005; Satpathy et al, 2005; Hartel FV et al, 2007). Conventional MLCP consist of a catalytic protein phosphatase 1 (PP1c) subunit, a myosin phosphatase targeting subunit (MYPT1), and a smaller M20 subunit, not always present in all the phosphatase complexes (Tar et al, 2006, Hartshorne et al, 1998; Takizawa et al, 2003; Ito et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Potential mechanisms for the PPP1 family include modulation of vascular permeability, cytoskeletal structure, and filopodia extension. PPP2A has been implicated in endothelial migration (Hartel et al, 2007; Li et al, 2007; Shinoki et al, 1995; Young et al, 2002). Moreover, Cantharidin, the 2, 3-dimethylanhydride of Endothall, has been shown to enhance endothelial-mediated contraction of arteries and endothelial permeability (Knapp et al, 1999, 2000).…”
Section: Discussionmentioning
confidence: 99%